A Comparative Clinical Study of Trikatu Churna and Pippali Churna in Artavakshaya w.s.r. to PCOS (International Journal of Ayurveda and Pharma Research, 2025)
Artavakshaya, a condition described in Ayurveda, is characterised by scanty and irregular menstruation, which closely correlates with the Polycystic Ovary Syndrome (PCOS). PCOS is a common endocrine disorder affecting reproductive-aged women, leading to menstrual irregularities, anovulation, and metabolic disturbances. Trikatu Churna, a combination of Pippali (Piper longum Linn.), Maricha (Piper nigrum Linn.), and Shunti (Zingiber officinale Roscoe.), is known for its Deepana, Pachana and Kaphavatahara properties, which may help in correcting metabolic imbalances associated with PCOS. Pippali Churna is recognized for its Rasayana and Lekhana actions, which may aid in improving ovarian function and hormonal balance. This study aims to compare the clinical efficacy of Trikatu Churna and Pippali Churna in managing Artavakshaya for PCOS. The effects of both formulations were evaluated based on clinical parameters such as duration of bleeding, irregular menstruation, amount of bleeding and quantity of menstrual blood, pain during the menstruation, hirsutism and BMI. This comparative clinical study was conducted on a total of 40 patients diagnosed with PCOS presenting with Artavakshaya symptoms and were randomly divided into two groups. Group A received Trikatu Churna, and Group B received Pippali Churna for 90 days. The primary outcome measures included improvements in duration of bleeding, irregular menstruation, amount of bleeding and quantity of menstrual blood, and pain during the menstrual period. The secondary outcomes included improvements in hirsutism and BMI. Both treatments showed significant improvements in the management of PCOS symptoms. However, Trikatu Churna was found to be slightly more effective in regulating menstrual cycles. This study suggests that Trikatu Churna and Pippali Churna can be beneficial in the management of Artavakshaya associated with PCOS, with Trikatu Churna showing marginally superior efficacy.